TOWARDS A PLURALISTIC PHILOSOPHY OF THE CONSERVATION OF CULTURAL HERITAGE - Genovese, Rosa Anna (BDC. Bollettino Del Centro Calza Bini, 2013)
The evaluation of cultural properties, intended in the full richness of their authenticity, must be taken into equal account for their material and non-material (Venice Charter, 1964). The Nara Declaration (1994) stresses that the definition and the assessment of the value of authenticity must be referred to a multicultural dimension. The destiny of cultural heritage is linked to the evolution of modern societies, seduced by the advance of technology, in which the destruction of ecological balance and the progression of egoistic materialism. It is necessary to call for an ever increasing participation in the building of an ethics adapted to the post-industrial world, enriching the socio-economic debate with the introduction of a humanistic vision nourished by the very sap of heritage. An effective policy for cultural properties supported by the participation and “conscious consensus” of the population can constitute the central instrument to ensure the economic, social and cultural development of the Regions of the world and to guarantee integrated conservation of cultural heritage.